Translation students’ peer feedback for learning English for Specific Purposes (ESP). Findings from a case study in Lithuania (Journal of Education Culture and Society, 2022)
Aim. The use of feedback (including peer-generated feedback) for learning has been widely investigated across many fields of study, however, no research into its use in Translation studies has been conducted yet. To fill in this gap, the present small-scale study was carried out at a university in Lithuania. It investigated undergraduate translation students’ feedback on their peers’ ESP oral performance by addressing the main research question: what areas are identified as those that need further work on?Methods. The present research was conducted with the participation of 42 undergraduate students who were majors in Translation studies. To carry out the research, qualitative methodology was chosen. The data were drawn from the study participants’ feedback sheets and investigated using inductive content analysis.Results.  The study resulted in the identification and detailed description of four major categories and ten subcategories that reflect the areas that call for further work on, including the study participants’ presentation content, the use of language, presentation delivery mode, and the use of slides.Conclusion. The findings lead to the conclusion that peer feedback, as used in this study, can be viewed as a tool providing its receivers with an opportunity for learning as it supports and directs them toward further improvement.